An Aggressive Primary Cutaneous Follicle Center Lymphoma With c-MYC Translocation and CDKN2A (9p21) Deletion: A Case Report and Review of the Literature. (March 2017) - Tsang, Hamilton C.; Mathew, Susan; Magro, Cynthia M.
Abstract: Diffuse large cell B-cell lymphoma of the skin is most commonly represented by diffuse large cell variants of primary cutaneous follicle center lymphoma and the leg-type lymphoma. In a minority of cases, the infiltrates are an expression of stage 4 disease of established extracutaneous B-cell lymphoma. We describe 1 female patient 85 years of age with an aggressive form of primary cutaneous B-cell lymphoma manifesting in multiple firm erythematous indurated solid nodules 1–2 cm each symmetrically on the face periorbitally and on the upper extremities bilaterally. The tumor was a de novo presentation of this aggressive form of lymphoma. The disease demonstrated an aggressive course with only transient improvement of skin lesions after chemotherapy. Punch biopsy taken from a left arm skin lesion showed a diffuse and nodular large cell lymphocytic infiltrate in the 15–20 μm range exhibiting round to oval nuclei and prominent eosinophilic nucleoli. Phenotypically, the tumor cells were CD10, Bcl-2, Bcl-6, and CD43 positive with a residuum of a follicular dendritic cell network revealed by CD21 staining. There was c-MYC rearrangement and CDKN2A deletion in this sample. The importance in reporting this case is to emphasize that in the context of primary cutaneous B-cell lymphoma, the 9p21 deletion while characteristic of the leg-type lymphoma is not a unique signature of the leg-type lymphoma and is not exclusionary to lymphomas falling under the designation of follicle center lymphoma. As with the leg-type lymphoma, however, this cytogenetic abnormality is a critical determinant to a more aggressive clinical course.